Vodovnikovi sodobniki na Kranjskem - Terseglav, Marko (Etnolog. Nova vrsta (Ljubljana), 2002)
Jurij Vodovnik (1791-1858) was a self-taught poet from Styria, whose songs have been preserved in the repertoires of folk singers until today, especiallyon Pohorje and in Štajerska. In this article the author attempts to find similar contemporaries in central Slovenia His research established thatthe teachers and organists Matevž Kračman (1773-1853) and Andrej Kančnik (1775-1841) from Dolenjska, whose songs have also become part of oral tradition, show many similarities. The author arguments that in folk poetry itdoes not really matter who or, even less, what the artist is (he or she may be either a self-taught person without any education or an intellectual ), butthat it much more important how poetic a song is, and that it must appeal to people, so that they can accept it as folk poetry. Terseglav considers these two folk artists to be a new challenge to Slovene folklore studies, because some scholars do not acknowledge similar (educated) artists to be folkartists or "real" folk poets. In his opinion, Slovene folklore studies will have to revise some of the views inherited from the 19th century.
Keywords: Vodovnik, Jurij, 1791-1858; Kračman, Matevž, 1773-1853; Kančnik, Andrej, 1775-1841; biografije; ljudsko pesništvo; ljudski pesniki